2014
DOI: 10.1103/physrevd.90.044022
|View full text |Cite
|
Sign up to set email alerts
|

Minding the gap in holographic models of interacting fermions

Abstract: We study the holographic dual of fermions interacting in a Schwarzschild-AdS d+1 background via a dipole (Pauli) coupling sourced by a probe gauge field. We find quite generally that a gap forms in the dual operator spectrum as the Pauli coupling is strengthened. Previous investigations have observed this behavior in analogous constructions with Reissner-Nordström-AdS (RN-AdS4) backgrounds, but the emergence of log-oscillatory behavior in those models' spectra prevented identification of the underlying gapping… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 24 publications
3
33
0
Order By: Relevance
“…These results had stimulated further studies [9][10][11][12][13][14][15][16] on the behaviour of the dipole coupling. A remarkable property was observed in [17] where it was found that there exists a duality between zeroes and poles in holographic systems with massless fermions and a dipole coupling and this property was also verified in [18].…”
Section: Jhep11(2014)086mentioning
confidence: 86%
“…These results had stimulated further studies [9][10][11][12][13][14][15][16] on the behaviour of the dipole coupling. A remarkable property was observed in [17] where it was found that there exists a duality between zeroes and poles in holographic systems with massless fermions and a dipole coupling and this property was also verified in [18].…”
Section: Jhep11(2014)086mentioning
confidence: 86%
“…In fact, any theory having an electron self energy with a diverging behavior at low frequency is likely to have a non-zero eV c . From the Dyson's equation, the self energy can be expressed as Σ = G graphic models 40,41 . As a result, it is expected that the same result will be obtained if these theories could be incorporated into T -matrix formalism to compute QPIs.…”
Section: As a Result T (ω) Can Be Evaluated Frommentioning
confidence: 99%
“…Such a term is well known to give rise to the anomalous magnetic moment of the electron in flat space. Even if the details of the bulk spacetime vary from Reissner-Nordstrom 32,33 to Schwarzschild 34 , as long as the spacetime at the boundary is asymptotically anti de Sitter, the fermionic propagator is gapped [32][33][34] as shown in Fig. (5) once p exceeds a critical value.…”
Section: Unparticles and Anti De Sitter Spacetimementioning
confidence: 99%
“…What this suggests is that within the general framework of the gauge-gravity duality, it should be possible to add various terms to the bulk gravity model which couple to the scaling dimension of the dual fermionic operators at the boundary to engineer propagators that exhibit zeros. Indeed, such a construction is possible [32][33][34] . Computing fermionic correlators at the boundary requires fermionic fields in the bulk described by an appropriate equation of motion.…”
Section: Unparticles and Anti De Sitter Spacetimementioning
confidence: 99%
See 1 more Smart Citation